Novel pre-copulatory behavior in basking sharks observed by drone. - Curtis, Tobey H; Robinson, Jeff; Pratt, Harold L; Skomal, Gregory B; Whitney, Nicholas M (Journal of Fish Biology, 2024)
Basking sharks (Cetorhinus maximus) seasonally aggregate in coastal surface waters of the North Atlantic, providing opportunities for visual observation. While putative courtship displays have been observed, actual copulation has not been documented. Here we examine video collected by an unmanned aerial vehicle ("drone") of novel behavioral interactions between basking sharks in Cape Cod Bay, Massachusetts in May 2021. The behaviors, including close following and tight concentric circling, are consistent with pre-copulatory behavior observed in other shark species. These observations provide new insights into the pre-copulatory behavior of basking sharks.